Responses of Diesel Engines to Ethanol Blended in Diesel-Biodiesel Blended Fuels - Tongroon, Manida; Chaisermtawan, Prateep; Thongchai, Sakda (Journal of Advanced Development in Engineering and Science, 2023)
This study has investigated the potential in the near future to use ethanol in a compression ignition engine or diesel engine without any engine modification. The selected engines tested are comprised of two types. The first one applies an in-line mechanical pump nozzle type which has been used in the past until now in the old vehicle and extendedly applied in the agricultural engines. The second one uses the high-pressure electronic common rail injection system, which is broadly used in modern diesel vehicles nowadays and in the future. Ethanol was used as the blend in diesel fuel with a concentration of 5 (E5) and 10 % (E10) by volume. To prevent a phase separation, biodiesel 3 (B3), 7 (B7), and 10 % (B10) by volume were added to diesel before adding the ethanol as an emulsifier for the blended fuels. Therefore, three ethanol-diesel-biodiesel blended fuels including B3E5, B7E5, and B10E10 were used in this study. The responses of the engines to the fuel were monitored in terms of torque, thermal efficiency, and exhaust gas emissions which were compared when using diesel B7, the standard diesel fuel in Thailand. The results found that ethanol-blended fuels could be used in both engines which respond to the test fuels in the same trend for almost all indicators. The types of injection systems partially contributed to the effect of ethanol on the engine operation. The use of ethanol-blended fuels, engine torque decreases for both engine types. However, a break thermal efficiency increases in the engine using mechanical pump system but there is no particular trend for the electronic injection system. Oxide of nitrogen and total hydrocarbon increase when using ethanol-diesel-biodiesel blends. The more the ethanol is blended, the higher the amount of nitrogen and total hydrocarbon are emitted from the engine with the mechanical type injection system. However, the engine using electronic injection control is not dependent on the ethanol concentration solely.